Desempenho do programa de pré-incubação como catalisador do empreendedorismo inovador - Frizzo, Kamila; Ferreira, Maria Carolina Zanini; Motke, Francies Diego; Gomes, Beatriz Maffini; Teixeira, Clarissa Stefani; Silva, Silon Júnior Procath da (Revista de Administração da UFSM, 2019)
In late 2014, the Federal University of Santa Maria (UFSM) created the Innovation and Technology Transfer Office (AGITTEC) with one of the goals to create a technology incubator. To achieve this, the university launched a pre-incubation program in order to train potential entrepreneurs. The program aimed to select technological development projects that had not yet found a company and required basic initial training. Therefore, the pre-incubation program and its performance among those involved (participants who completed the program, mentors, and lecturers) were analyzed and described in a descriptive and quali-quantitative manner. Questionnaires for performance analysis of the services provided were elaborated from the structure and program activities and composed of closed questions in which respondents indicated on an interval scale of 1 to 5 (lowest to highest level of assessment) or the option “does not apply” (represented by the number zero). The results concluded that the pre-incubation program was essential for all participating projects by showing which activities should be prioritized in future programs.